2019
DOI: 10.1038/s41598-019-47033-7
|View full text |Cite
|
Sign up to set email alerts
|

USP10 is a critical factor for Tau-positive stress granule formation in neuronal cells

Abstract: Tau aggregates in neurons of brain lesions is a hallmark pathology of tauopathies, including Alzheimer’s disease (AD). Recent studies suggest that the RNA-binding protein TIA1 initiates Tau aggregation by inducing the formation of stress granules (SGs) containing Tau. SGs are stress-inducible cytoplasmic protein aggregates containing many RNA-binding proteins that has been implicated as an initial site of multiple pathogenic protein aggregates in several neurodegenerative diseases. In this study, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…Exposing HT22 neuronal cells to stress resulted in the formation of TIA1/Tau-positive stress granules that were severely attenuated by depletion of USP10. In this study, USP10 colocalized with Tau aggregates in the “cell body” of neurons in AD brain lesions suggesting that USP10 is important for stress granule formation in Tau pathology 85 .…”
Section: Usp10 In Alzheimer’s Disease and Other Neurodegenerative Dissupporting
confidence: 54%
“…Exposing HT22 neuronal cells to stress resulted in the formation of TIA1/Tau-positive stress granules that were severely attenuated by depletion of USP10. In this study, USP10 colocalized with Tau aggregates in the “cell body” of neurons in AD brain lesions suggesting that USP10 is important for stress granule formation in Tau pathology 85 .…”
Section: Usp10 In Alzheimer’s Disease and Other Neurodegenerative Dissupporting
confidence: 54%
“…Tau is reported to co‐localize with SG‐associated RBPs, 196 which might lead to the maturation into obstinate pathological SGs during stress. The association of ubiquitin with neurofibrillary tangles is also well documented, 197 in line with shreds of evidence related to Ubiquitin‐specific protease 10 (USP10) as a crucial factor for the formation of SGs comprising tau, TIA‐1, and USP10 198 . USP10 also colocalizes with aggregated tau in AD patients' brain lesions, 198 suggesting its role in SG mediated tau aggregation.…”
Section: Phase Transitions Of Tau In Physiology and Diseasementioning
confidence: 55%
“…The association of ubiquitin with neurofibrillary tangles is also well documented, 197 in line with shreds of evidence related to Ubiquitin‐specific protease 10 (USP10) as a crucial factor for the formation of SGs comprising tau, TIA‐1, and USP10 198 . USP10 also colocalizes with aggregated tau in AD patients' brain lesions, 198 suggesting its role in SG mediated tau aggregation. At the same time, it was found that acetylation decreases the SG‐association of tau 125 .…”
Section: Phase Transitions Of Tau In Physiology and Diseasementioning
confidence: 55%
“…A relationship between tau and stress granules has been reported (Apicco et al, 2018 ; Piatnitskaia et al, 2019 ) in which T-cell intracellular antigen-1 (TIA-1), a DNA/RNA-binding protein transferred from the nucleus to the cytoplasm during stress may play an important role (Kedersha et al, 2000 ). In fact, TIA-1 co-localizes with pathological tau in human tissue from AD patients (Vanderweyde et al, 2012 ), and a 50% reduction in TIA-1 expression of cytoplasmic stress granules in P301S tau transgenic (PS-19) mice leads to improvements in behavior and lifespan in parallel with reduced neuronal and synaptic degeneration (Apicco et al, 2018 ).…”
Section: New Tau-target Therapy For Tauopathiesmentioning
confidence: 99%